2017
DOI: 10.1007/s13187-017-1254-z
|View full text |Cite
|
Sign up to set email alerts
|

Is Cancer Information Exchanged on Social Media Scientifically Accurate?

Abstract: Cancer patients and their caregivers are increasingly using social media as a platform to share cancer experiences, connect with support, and exchange cancer-related information. Yet, little is known about the nature and scientific accuracy of cancer-related information exchanged on social media. We conducted a content analysis of 12 months of data from 18 publically available Facebook Pages hosted by parents of children with acute lymphoblastic leukemia (N = 15,852 posts) and extracted all exchanges of medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 27 publications
1
57
0
10
Order By: Relevance
“…Social media sites clearly influence people's health‐related perceptions and offer powerful tools for improving the health of both people and animals. Yet these sites, and their lack of gatekeepers, can also misinform people about both human and animal health‐related topics . The open‐ended questions in the current study illustrate both the potential benefits and pitfalls of social media for accessing health‐related topics.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Social media sites clearly influence people's health‐related perceptions and offer powerful tools for improving the health of both people and animals. Yet these sites, and their lack of gatekeepers, can also misinform people about both human and animal health‐related topics . The open‐ended questions in the current study illustrate both the potential benefits and pitfalls of social media for accessing health‐related topics.…”
Section: Discussionmentioning
confidence: 89%
“…Yet these sites, and their lack of gatekeepers, can also misinform people about both human and animal health-related topics. [13][14][15] The open-ended questions in the current study illustrate both the potential benefits and pitfalls of social media for accessing health-related topics. A relatively new line of research in human medicine in which social media is utilised to correct misinformation 15 might be of benefit to veterinary medicine as well.…”
Section: Discussionmentioning
confidence: 99%
“…With an increasing number of investigations (i.e., genomic and tumor molecular profiling studies) and treatment options (i.e., clinical trials) available for cancer-care and a growing population of cancer survivors, accessing cancer-related online health information is expected to rise [39,40]. Patients will often consult additional sources of information other than their health care providers [41], raising concerns of patient misinterpretation of online information, information accuracy, and false information being exchanged on social media and the internet [2,42,43]. Oncology healthcare providers are in a unique position given their relationship with patients to help guide them on medical decision making and interpreting online information.…”
Section: Discussionmentioning
confidence: 99%
“…Health information posted online by patients is in abundance and is often publicly available, thus representing an untapped source of post-market safety data that could supplement data from existing sources of medicine safety information [22,156]. For example, the study by Gage-Bouchard et al [23] on cancer information exchanged on personal Facebook Pages revealed that this information predominantly related to treatment protocols and health services use (35%), followed by information related to side effects and late effects (26%) and medication (16%).…”
Section: Pharmacovigilance Backgroundmentioning
confidence: 99%